Innovation in Propagation of Fruit, Vegetable and Ornamental Plants - Roberto, Sergio Ruffo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In horticulture, plant propagation plays an important role, as the number of plants can be rapidly multiplied, retaining the desirable characteristics of the mother plants, and shortening the bearing age of plants. There are two primary forms of plant propagation: sexual and asexual. In nature, the propagation of plants most often involves sexual reproduction, and this form is still used in several species. Over the years, horticulturists have developed asexual propagation methods that use vegetative plant parts. Innovation in plant propagation has supported breeding programs and allowed the production of high quality nursery plants with the same genetic characteristics of the mother plant, free of diseases or pests.